Brugada phenocopy caused by a compressive mediastinal tumor. Issue 3 (15th October 2017) - Pérez‐Riera, Andrés R.; Barbosa Barros, Raimundo; Daminello‐Raimundo, Rodrigo; Resende Barbosa, Marianne P. C.; de Abreu, Luiz C.
Abstract : Recently, it has been shown that even experts in electrocardiography cannot differentiate the electrocardiographic pattern of genuine Brugada syndrome (BrS) from Brugada phenocopy (BrP). For this reason, this differentiation depends on the presence of established criteria both for BrS and BrP. In this manuscript, we present a patient with type 1 Brugada electrocardiographic pattern caused by expansive anterior mediastinal non‐Hodgkin's lymphoma (NHL) with mechanical compression on the right ventricular outflow tract. The electrocardiographic pattern disappeared rapidly after antineoplastic measures.